Preliminary design study of Long-life Gas Cooled Fast Reactor With Modified CANDLE Burnup Scheme - Nur Asiah A; Merry Yanti; Zaki Su’ud; Menik A.; H. Sekimoto (Institut Teknologi Bandung, 2009)
In this paper, preliminary design study of Gas Cooled Fas Reactors with Natural Uranium as Fuel Cycle Input has been performed. Gas Cooled Fast Reactor is slightly modified by employing modified CANDLE burnup scheme so that it can use Natural Uranium as fuel cycle input. The natural uranium is initially put in region 1, after one cycle of 10 years of burn-up it is shifted to region 2 and the region 1 is filled by fresh natural uranium fuel. This concept is basically applied to all regions. In this case the system has been applied to many power level which results relatively flexible discharge burn-up level up from about 20%HM to 30 %HM.